(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
This paper discussed the impact of the Tertiary Education Trust Fund (TETFUND) on Tertiary Education Development in Nigeria. The paper employed secondary data. The data were collected from both print and online publications. The paper concluded that Tertiary Education Trust Fund (TETFUND) has contributed immensely to the development of infrastructure facilities, human resources, and research programmes and intervened in the provision of funds for tertiary education management in Nigeria. Based on these findings, the paper suggested that Tertiary Education Trust Fund (TETFUND) should establish offices in all six geo-political zones in Nigeria for effective and efficient operation in the tertiary institutions. More tertiary education stakeholders (ASUU, ASUP and ASUCOE) should be involved in the management of the funds. Tertiary Education Trust Fund (TETFUND) should invest some of their funds to raise more funding for the infrastructure development of the tertiary institutions in Nigeria.